2006
DOI: 10.1590/s1517-83822006000300036
|View full text |Cite
|
Sign up to set email alerts
|

Keratinolytic bacteria isolated from feather waste

Abstract: The aim of this study was to characterize keratinolytic bacteria isolated from feather waste. Four isolates were selected after growth on solid medium with feather meal as sole carbon and nitrogen source and screened for proteolytic activity on milk agar plates. Three isolates were Gram-negative (belonged to the genera Burkholderia, Chryseobacterium and Pseudomonas) and one was Gram-positive (Microbacterium sp.). These bacteria grew on diverse keratin wastes such as feather meal, raw feathers, chicken nails, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(88 citation statements)
references
References 27 publications
5
76
0
3
Order By: Relevance
“…Microbe-induced feather degradation can potentially hinder flight (when wing feathers are involved) and mate attraction (when plumage condition or colour is important for mate selection), as well as thermoregulation [10,11,52]; although the extent and magnitude of such effects is currently unknown [24]. Keratinolytic microbes previously associated with birds include the bacterium Bacillus licheniformis [47] and the fungi Chrysosporium tropicum and Microsporum gallinae [27].…”
Section: Introductionmentioning
confidence: 99%
“…Microbe-induced feather degradation can potentially hinder flight (when wing feathers are involved) and mate attraction (when plumage condition or colour is important for mate selection), as well as thermoregulation [10,11,52]; although the extent and magnitude of such effects is currently unknown [24]. Keratinolytic microbes previously associated with birds include the bacterium Bacillus licheniformis [47] and the fungi Chrysosporium tropicum and Microsporum gallinae [27].…”
Section: Introductionmentioning
confidence: 99%
“…Plate assays were attempted on keratin powder plates by Nocardiopsis sp.TOA-1 where they formed extremely large ones on the plate (Mitsuiki et al, 2002). Milk agar medium was used for the primary screening of actinobacteria (Riffel and Brandelli, 2006). Another author discussed the primary screening of keratinolytic actinobacteria isolated from keratin waste dumped soil in Thiruchirapalli and Namakkal, Tamilnadu, India using milk agar medium (Saha and Dhanasekaran, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Milk agar and soya meal agar medium were used for the primary screening of keratinolytic actinobacteria (Riffel and Brandelli, 2006). After sterilization, the media were poured into sterile Petri dishes.…”
Section: Primary Screening Of Keratinolytic Actinobacteriamentioning
confidence: 99%
“…It was clear that presence of feather in the growth medium act as an enzyme inducer. Riffel and Brandelli (2006) reported that keratinase producing bacteria had different characteristics, such as a broad temperature range of growth. The optimal proteolytic activities were detected between 30 and 37°C (Atalo and Gashe, 1993).…”
Section: Discussionmentioning
confidence: 99%